Are there moral differences between maternal spindle transfer and pronuclear transfer? - Palacios-González, C (Springer, 2017)
This paper examines whether there are moral differences between the mitochondrial replacement techniques that have been recently developed in order to help women afflicted by mitochondrial DNA diseases to have genetically related children absent such conditions: maternal spindle transfer (MST) and pronuclear transfer (PNT). Firstly, it examines whether there is a moral difference between MST and PNT in terms of the divide between somatic interventions and germline interventions. Secondly, it considers whether PNT and MST are morally distinct under a therapy/creation optic. Finally, it investigates whether there is a moral difference between MST and PNT from a human embryo destruction point of view. I conclude, contra recent arguments, that regarding the first two points there is no moral differences between PNT and MST; and that regarding the third one MST is morally preferable to PNT, but only if we hold a gradualist account of the moral value of human embryos where zygotes have slight moral value.